Delayed Surgical Management of the Patients with Chronic Dacryocystitis: A Cross Sectional Survey: Doi: 10.36351/pjo.v38i2.1305 - Batool, Bazla; Iqbal, Usama; Iqbal, Hamza; Malik, Irfan Qayyum; Jabran, Aamna (Pakistan Journal of Ophthalmology, 2022)
Purpose: To determine the factors that cause delay in Dacryocystorhinostomy in patients with chronic dacryocystitis. Study Design: Cross sectional survey. Place and Duration of Study: Ophthalmology Department DHQ Teaching Hospital Gujranwala from February 2021 to May 2021 Methods: Sixty five ophthalmologists were included in this study. Questionnaire was designed on Google Forms and it composed of four parts. First part included the title and purpose of this study. Second part included professional information regarding qualification and place of practice. Third part included 18 questions that were divided in three sub-sections in terms of factors related to the patient (5 questions), ophthalmologist (9 questions), and health resources provided (4 questions). Responses were recorded in yes/no answers. Last part comprised of blank space for remarks. The electronic link of questionnaire was shared with the participants of ophthalmology educational groups on WhatsApp, Facebook and E-mail. Data was analyzed using SPSS 23.00 software and results were derived based on questionnaire. Results: Out of 65 ophthalmologists, 48 (72.7%) agreed that patients suffered from delay in surgical management. Among the hospital related factors, 45 (69.23%) ophthalmologists believe that busy Out patient department accounted for most of the delay. Among patient related factors, 51 (78.46%) ophthalmologists were of the view that patients took the disease lightly as it was not vision-threating. Forty one ophthalmologists (63.07%) reported that there was lack of surgical exposure during training years to learn DCR. Conclusion: There are various patient related, surgeon related and hospital related factors which play a significant role in delay of surgical management of chronic dacryocystitis. Key Words: Dacryocystitis, Dacryocystorhinostomy, Epiphora.